PENGARUH KUAT-LEMAHNYA BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI (Suatu Kajian Terhadap Teori Budaya Organisasi Robbins) - Teni Listiani, (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
The performance of the whole employees in an organization can be seen from theirbehavior both individually or collectively. This behavior can generally affected by theorganization characteristics reflected in its organization culture. Robin’s theory states that the level of staffs performance will be greatly affected by the strengths and, weaknesses of the organization culture. An organization with strong culture usually has similar core values agreed upon by most of the organization members. In addition, in an organization with strong culture, its employees usually has very high commitment towards the values. The stronger the culture of an organization is, the higher the commitment of the employees towards the core values will be. Thiscommitment will affect the behavior of its members reflected through theirperformance. Similarly, in an organization with weak culture, the commitment of itsmembers to its core values will be low too. Therefore its effect towards work behavior will not be significant (low performance).